The effect of pre-exercise alkalosis on lactate/pH regulation and mitochondrial respiration following sprint-interval exercise in humans - Thomas, Claire; Delfour‐Peyrethon, Rémi; Lambert, Karen; Granata, Cesare; Hobbs, Thomas; Hanon, Christine; Bishop, David J. (Frontiers in Physiology, 2023)
The purpose of this study was to evaluate the effect of pre-exercise alkalosis, induced via ingestion of sodium bicarbonate, on changes to lactate/pH regulatory proteins and mitochondrial function induced by a sprint-interval exercise session in humans. On two occasions separated by 1 week, eight active men performed a 3 x 30-s all-out cycling test, interspersed with 20 min of recovery, following either placebo (PLA) or sodium bicarbonate (BIC) ingestion. Blood bicarbonate and pH were elevated at all time points after ingestion in BIC vs PLA (P < 0.05). The protein content of monocarboxylate transporter 1 (MCT1) and basigin (CD147), at 6 h and 24 h post-exercise, and sodium/hydrogen exchanger 1 (NHE1) 24 h post-exercise, were significantly greater in BIC compared to PLA (P < 0.05), whereas monocarboxylate transporter 4 (MCT4), sodium/bicarbonate cotransporter (NBC), and carbonic anhydrase isoform II (CAII) content was unchanged. These increases in protein content in BIC vs PLA after acute sprint-interval exercise may be associated with altered physiological responses to exercise, such as the higher blood pH and bicarbonate concentration values, and lower exercise-induced oxidative stress observed during recovery (P < 0.05). Additionally, mitochondrial respiration decreased after 24 h of recovery in the BIC condition only, with no changes in oxidative protein content in either condition. These data demonstrate that metabolic alkalosis induces post-exercise increases in several lactate/pH regulatory proteins, and reveal an unexpected role for acidosis in mitigating the loss of mitochondrial respiration caused by exercise in the short term.